PESTEL ANALYSIS: WOMAN AND THE PORTUGUESE LABOUR MARKET AFTER 25 APRIL 1974 - Lucas, Laura de Castro (2022)
Women have seen their role in the Portuguese labour market grow and gain prominence since the Carnation Revolution, in April 1974. The composition of this article was based on literature review and the collection of secondary data through databases, and it was through these that the PESTEL analysis was developed. This study sought to understand how society was impacted by Women in the Portuguese labour market since the end of the Estado Novo regime and how the labour market was influenced by their presence, as well was to understand what can still be done to improve their position.